2022
DOI: 10.1007/s40333-022-0057-1
|View full text |Cite
|
Sign up to set email alerts
|

Ecological environment quality evaluation of the Sahel region in Africa based on remote sensing ecological index

Abstract: Long-term monitoring of the ecological environment changes is helpful for the protection of the ecological environment. Based on the ecological environment of the Sahel region in Africa, we established a remote sensing ecological index (RSEI) model for this region by combining dryness, moisture, greenness, and desertification indicators. Using the Moderate-resolution Imaging Spectroradiometer (MODIS) data in Google Earth Engine (GEE) platform, this study analyzed the ecological environment quality of the Sahel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 82 publications
0
14
0
Order By: Relevance
“…In order to comprehensively monitor the ecological environment, it is usually necessary to obtain more information of ground targets with the help of geographic information system (GIS) and global positioning system (GPS). rough the integration of RS, GIS and GPS technology, we can accurately obtain the target attribute information and location information of the ground ecological area, and establish a spatial information database based on the superposition processing and statistical analysis of the spatial data, so as to effectively manage and query the spatial data [18].…”
Section: Remote Sensing Data Source Of Ecological Environmentmentioning
confidence: 99%
“…In order to comprehensively monitor the ecological environment, it is usually necessary to obtain more information of ground targets with the help of geographic information system (GIS) and global positioning system (GPS). rough the integration of RS, GIS and GPS technology, we can accurately obtain the target attribute information and location information of the ground ecological area, and establish a spatial information database based on the superposition processing and statistical analysis of the spatial data, so as to effectively manage and query the spatial data [18].…”
Section: Remote Sensing Data Source Of Ecological Environmentmentioning
confidence: 99%
“…The total area of Chabuga mining area was known through the survey as 4.31km 2 , and the specific grading table is shown in Table 4 below [12] . By using the raster data classification that comes with ENVI, the area corresponding to different stratification in the RSEI image can be calculated [13], as follows Table 5 shows the statistics of the area of the whole mine ecological environment grading, the broken ring inside the mine is serious, and the surrounding ecological environment is affected accordingly, before the ecological restoration project was carried out in 19 years, the area of the local ecological environment that is above medium (Grade 3~5) in the grading was counted a total of 2181670m 2 , accounting for 16.9% of the overall area, the area of the part of poor ecological environment(Grade 1~2) totaled 10791478m 2 , accounting for 83.1% of the total statistical area, and after the ecological restoration project in 2022, the area of the part of the with ecological grade above medium was only 31%, while the part of poor ecological environment totaled 69% of the area. The area of the ecological grade above medium expands from 2181670m 2 to 4025701m 2 , and the mean value of RSEI increases from 0.56509 in 19 years to 0.69072 in 22 years, from the data it can be observed that the effect of the ecological project has achieved some results and the ecological environment of the study area is gradually improved.…”
Section: Analysis Of Spatial and Temporal Variation Of Remote Sensing...mentioning
confidence: 99%
“…The grading of evaluation indicators in ecological sensitivity assessment is an important link in related research. This article refers to previous research by relevant scholars [15][16] and divides the levels of various evaluation indicators into four levels: insensitive, low sensitive, moderately sensitive, and highly sensitive, with corresponding quantification scores of 1.3.5.7 assigned from low to high.…”
Section: Grading and Weight Assignmentmentioning
confidence: 99%